FIQH AL-HADIS الْقُضَاةُ ثَلاَثَةٌ (HAKIM ADA TIGA GOLONGAN) - Siti Ardianti (SHAHIH (Jurnal Ilmu Kewahyuan), 2022)
Fiqh al-hadith is a study that tries to explore and understand the teachings contained in the hadiths of the Prophet so that they can be practiced. Fiqh al-Hadis in language is 'understanding the matan hadith'. Meanwhile, conceptually, Fiqh al-Hadis is a concept of thought that responds to the demands of the times and society, in accordance with the sunnah of the Prophet Muhammad. In this paper, the focus is on the quiet discussion of judges, there are three groups. Judges are required to have noble moral integrity (personal integrity), in the form of honesty and good personality. In carrying out his duties a judge must adhere to the principles of Faith, Islam and Ihsan, because these three things cannot be separated from one another, because this is where moral ethics is born to serve as a guide and guide for him; People who have strong faith will also have strong self-esteem and will not commit acts that are prohibited by religion, they will not be shaken by anything related to their profession.